2017
DOI: 10.1177/1753193417693170
|View full text |Cite
|
Sign up to set email alerts
|

Distal radioulnar joint: functional anatomy, including pathomechanics

Abstract: The distal radioulnar joint allows the human to rotate the forearm to place the hand in a desired position to perform different tasks, without interfering with the grasping function of the hand. The ulna is the stable part of the forearm around which the radius rotates; the stability of the distal radioulnar joint is provided by the interaction between ligaments, muscles and bones. The stabilizing structures are the triangular fibrocartilage complex, the ulnocarpal ligament complex, the extensor carpi ulnaris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 47 publications
0
52
0
9
Order By: Relevance
“…The TFCC, containing superficial and deep fibers, is the main stabilizer of the DRUJ [32]. Many studies concluded that the dorsal superficial fibers tighten in pronation, as do the deep palmar fibers and vice versa [31]. Therefore, we speculate that the relative decrease in pronation and supination is associated with insufficient reconstruction of Fig.…”
Section: Comparison Of Range Of Motion (Rom)mentioning
confidence: 82%
See 1 more Smart Citation
“…The TFCC, containing superficial and deep fibers, is the main stabilizer of the DRUJ [32]. Many studies concluded that the dorsal superficial fibers tighten in pronation, as do the deep palmar fibers and vice versa [31]. Therefore, we speculate that the relative decrease in pronation and supination is associated with insufficient reconstruction of Fig.…”
Section: Comparison Of Range Of Motion (Rom)mentioning
confidence: 82%
“…Based on the tumor border, most structures of the triangular fibrocartilage complex (TFCC) were not preserved in the four patients; therefore, there was a tendency for separation of the DRUJ. With respect to the stabilizing structures of the DRUJ, which includes the TFCC, surrounding ligament, tendon, muscle, interosseous membrane, the bone itself, and the capsule [31]. The TFCC, containing superficial and deep fibers, is the main stabilizer of the DRUJ [32].…”
Section: Comparison Of Range Of Motion (Rom)mentioning
confidence: 99%
“…This area is sometimes referred to as the ligament subcruentum 3 4. Studies show that on pronation and supination, the radioulnar ligaments tighten,5 although in which direction tightening occurs is an area of debate. One study found the volar radioulnar ligament to be taught in pronation and the dorsal ligament in supination 6.…”
Section: Anatomy and Functionmentioning
confidence: 99%
“…1, Volar ulnocarpal ligaments; 2, meniscus homologue; 3, fibrocartilage disc; 4, dorsal distal radioulnar ligament; 5, extensor carpi ulnaris sheath; 6, distal oblique band of the interosseous ligament. (Reproduced with permission from Haugstvedt et al 5). …”
Section: Anatomy and Functionmentioning
confidence: 99%
“…Presence of double head of PQ muscle was reported by Jadhave et al in 2014. Absence of PQ in Madelung's deformity of the wrist was reported by Haugstvedt et al in 2017. Anomalous variations of PQ muscle is widely appreciated as the diagnosis and treatment of pronator quadratus myofascial pain syndrome associated with the variations (Lee & Idler 1996).…”
mentioning
confidence: 99%